Penggunaan Media Digital Marketing Sebagai Media Promosi Pada Akun @hijup.com (Studi Etnografi Virtual Pada Akun Instargam - Khoerunnisa Khoerunnisa; Ida Ri'aeni; Rizki Budhi Suhara (JIKA (Jurnal Ilmu Komunikasi Andalan), 2021)
With the advent of the internet, the development of marketing to a new level, marketing through the internet is called digital marketing. This study discusses the digital marketing media strategy carried out by HijUp.com. HijUp.com is a fashion e-commerce company that is successful in gaining sales. This study aims to explain how the analysis of Hijup.com's digital marketing media strategy is centered on Instagram social media. In this research approach, the author uses a virtual ethnography study which is widely used in online research. The research subject is focused on examining the experiences of users of the snapgram feature. The technique that will be used in selecting informants or subjects will be chosen purposively based on their activities that can explore and articulate their experiences consciously, which are used as key informants or main data sources or Creswell calls them participants. Data collection was obtained from key informants or main data sources as participants through online interviews. The data obtained are arranged in one unit and then categorized and coding is carried out. Based on the results of Hijup.com's research, it involves digital roles starting from the marketing mix and using concepts in the form of visuals, designs and captions. and digital marketing in almost all marketing and sales activities HijUp.com markets its products online by optimizing digital marketing tools in an integrated manner. The use of digital media really helps HijUp.com in carrying out its marketing functions efficiently and effectively.